Eltrombopag Can Achieve Treatment Free Remission as Upfront Therapy for Patient with Immune Thrombocytopenia. (April 2021) - Obeidat, Khaldun; Yassin, Mohamad A
Immune Thrombocytopenic purpura (ITP) is an immune mediated thrombocytopenia caused by autoantibodies directed against platelet antigens which leads to destruction of the platelets by the spleen and inability of the bone marrow to restore normal counts. The main treatment for ITP is immunosuppressive medication and the first line treatment is glucocorticoids, intravenous immune globulin (IVIG) and Intravenous anti-D immune globulin. Here we report a 45-year old lady who was diagnosed with ITP and achieved treatment free remission after with Eltrombopag as upfront.